Resonant Soft X-Ray Inelastic Scattering and Soft X-Ray Emission Study of the Electronic Structure of alpha-MoO3 - MCGUINNESS, CORMAC (My University, 2009)
The electronic structure of quasi-low-dimensional solids is a topic of enduring interest due to the complex many-body interactions that exist in such materials and their resulting exotic physical properties. A well studied class of such materials is the quasi-low-dimensional metals known collectively as molybdenum oxide bronzes. These materials are all derived from the band insulator -MoO 3 . We report here a study of the electronic structure of -MoO 3 using resonant inelastic x-ray scattering and soft x-ray emission spectroscopy. We observe significant variation in x-ray scattering as a function of the relative orientation of the polarization vector of the incident light and the crystal axes. We interpret our data using a model of k -selective soft x-ray scattering
PUBLISHED
Keywords: quasi-low-dimensional solids; quasi-low-dimensional solids; Nanoscience & Materials